2007
DOI: 10.1039/b601326k
|View full text |Cite
|
Sign up to set email alerts
|

Chip integrated strategies for acoustic separation and manipulation of cells and particles

Abstract: Acoustic standing wave technology combined with microtechnology opens up new areas for the development of advanced particle and cell separating microfluidic systems. This tutorial review outlines the fundamental work performed on continuous flow acoustic standing wave separation of particles in macro scale systems. The transition to the microchip format is further surveyed, where both fabrication and design issues are discussed. The acoustic technology offers attractive features, such as reasonable throughput … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
629
0
14

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 778 publications
(647 citation statements)
references
References 46 publications
4
629
0
14
Order By: Relevance
“…Thus, the primary acoustic radiation force will be enhanced and easier to drive the metal hollow nanostructures into the levitation plane. Due to the alloy frame density and its compressibility,23, 49 we also found that the secondary forces arising from the acoustic particle to particle interaction became much more significant, as shown in Video S7 (Supporting Information). The net effect of the primary and secondary acoustic radiation forces makes the acoustic levitation and swarm aggregations of the metal hollow nanostructures to be easily realized at low energy and clinically acceptable acoustic frequency.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations
“…Thus, the primary acoustic radiation force will be enhanced and easier to drive the metal hollow nanostructures into the levitation plane. Due to the alloy frame density and its compressibility,23, 49 we also found that the secondary forces arising from the acoustic particle to particle interaction became much more significant, as shown in Video S7 (Supporting Information). The net effect of the primary and secondary acoustic radiation forces makes the acoustic levitation and swarm aggregations of the metal hollow nanostructures to be easily realized at low energy and clinically acceptable acoustic frequency.…”
Section: Discussionmentioning
confidence: 77%
“…The results indicate that the size parameter is not important for acoustic manipulation when the particle size is much smaller than the acoustic wavelength. According to the previous theory,23, 24, 45, 46, 47, 48 the primary acoustic radiation force F on small particles can be calculated as Equation (1) Fmax=πP2VnormalP2λ1ρnormalMCnormalM25ρP2ρM2ρP+ρMρMCM2ρPCP2where P is acoustic pressure, V P is the volume of metal particle, ρ P and ρ M are the density of metal particle and medium, C P and C M are the speed of sound in particle and medium, respectively. Details are listed in Table S1 (Supporting Information).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depending on the application, their simpler channel geometry and faster manipulation speed may outweigh the complications of integrating electrodes in their designs. For example, acoustophoresis can separate particles and cells according to their size, density, as well as compressibility (Laurell et al 2007;Shi et al 2009;Wang and Zhe 2011). Dielectrophoresis (DEP), arising from interactions of cells' dipoles and their surrounding electric fields, can realize low-cost and integrated devices for cell manipulation (Voldman 2006).…”
Section: Introductionmentioning
confidence: 99%